Bilateral effect of aging population on consumption structure: Evidence from China - Wang, Yue; Zhao, Wan; Meng, Wanrong (Frontiers in Public Health, 2022)
The deepening of aging population inevitably in China will exert a far-reaching influence on national consumption and economic transformation. Based on interprovincial panel data in 2000–2018, this paper measured the ratio of five survival and enjoyment consumptions in disposable incomes, reconstructed the indicators for upgrading the consumption structure, used the bilateral stochastic cutting-edge model, and decomposed the aging population to realize the net effect from the positive and negative effects generated by the consumption structure. The findings indicated that (1) aging population played a positive and negative bilateral effect on upgrading the consumption structure, in which the positive effect upgraded 14.04% of the consumption structure while the negative effect degraded 6.18% of the consumption structure. The comprehensive net effect upgraded 7.86% of the consumption structure. (2) From the perspective of the time effect, under the positive and negative effects of aging population, the consumption structure was upgraded 7.861% on average every year. (3) Regarding the regional effect, the promotion role of aging population was the highest in the eastern region, followed by the west. The middle was the lowest. By combining with estimation results of each province, the promotion role brought by aging population in the northeast and southwest was lower. Based on the above-mentioned research results, this paper proposed some advice for positively developing silver hair economy, promoting the improvement on the consumption structure according to circumstances, developing the perfect aging consumption market, exploring the consumption potential of the elderly, accelerating the urbanization development progress, and stimulating consumption growth relying on the Internet.